Waste Heat Recovery from Diesel Engine Exhaust Using a Single-Screw Expander Organic Rankine Cycle System: Experimental Investigation of Exergy Destruction - Yeqiang Zhang (Energies, 2020)
The organic Rankine cycle is a mature small-scale power generation technology for harnessing low- to mid-temperature heat sources. However, the low efficiency of the cycle still hinders its widespread implementation. To optimize the cycle’s performance, it is crucial to identify the source and magnitude of losses within each component of the cycle. This study, thus, aims to investigate the irreversible losses and their effect on the performance of the system. A prototype organic Rankine cycle (ORC) with the exhaust of a diesel engine as the heat source was developed to experimentally investigate the system and ascertain the losses. The experiments were performed at steady-state conditions at different evaporation pressures from 1300 kPa to 1600 kPa. The exergy loss and exergetic efficiency of the individual component and the overall system was estimated from the experimentally measurement of the pressure, temperature, and mass flow rate. The results indicate that the exergy losses of the evaporator are almost 60 kW at different evaporation pressures and the exergy loss rate is from 69.1% to 65.1%, which accounted for most of the total exergy loss rate in the organic Rankine cycle system. Meanwhile, the highest shaft efficiency and exergetic efficiency of the screw expander are 49.8% and 38.4%, respectively, and the exergy losses and exergy loss rate of the pump and pipe are less than 0.5 kW and 1%. Due to the relatively higher exergy loss of the evaporator and the low efficiency of expander, the highest exergetic efficiency of the organic Rankine cycle system is about 10.8%. The study concludes that the maximum improvement potential lies in the evaporator, followed by the expander.